2004
DOI: 10.1021/cm0349250
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Platinum and Palladium/Polyimide Nanocomposite Film as a Precursor of Metal-Doped Carbon Molecular Sieve Membrane via Supercritical Impregnation

Abstract: The synthesis of a Pt-and Pd-nanoparticle-dispersed polyimide film as a precursor for the preparation of a metal-doped carbon molecular sieve (CMS) membrane for hydrogen separation has been performed. Impregnation of Pt(II) acetylacetonate and Pd(II) acetylacetonate dissolved in supercritical CO 2 yielded Pt and Pd nanoparticles (diameters 12 and 5 nm, respectively) that were highly dispersed inside polyimide films under optimized conditions. The impregnation temperature and varieties of polyimide films strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(70 citation statements)
references
References 13 publications
3
67
0
Order By: Relevance
“…Namely, the concept of composite carbon molecular sieve membranes (c-CMSM) -incorporation of nanoparticles in the carbon matrix -has appeared as an alternative to improve the permeation performance, chemical and thermal stability of CMSM (Barsema et al, 2003(Barsema et al, , 2005Liu et al, 2006Liu et al, , 2009Park et al, 2004Park et al, , 2005Teixeira et al, 2011Teixeira et al, , 2012Xiao et al, 2010;Yin et al, 2010;Yoda et al, 2004;Zeng et al, 2008). Kim et al (2002Kim et al ( , 2003 prepared c-CMSM from metal-substituted sulfonated polyimides and observed that the permeabilities increased with the ionic radius of the metal ions (Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, the concept of composite carbon molecular sieve membranes (c-CMSM) -incorporation of nanoparticles in the carbon matrix -has appeared as an alternative to improve the permeation performance, chemical and thermal stability of CMSM (Barsema et al, 2003(Barsema et al, , 2005Liu et al, 2006Liu et al, , 2009Park et al, 2004Park et al, , 2005Teixeira et al, 2011Teixeira et al, , 2012Xiao et al, 2010;Yin et al, 2010;Yoda et al, 2004;Zeng et al, 2008). Kim et al (2002Kim et al ( , 2003 prepared c-CMSM from metal-substituted sulfonated polyimides and observed that the permeabilities increased with the ionic radius of the metal ions (Kim et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Barsema et al (2003Barsema et al ( , 2005 dispersed Ag nanoparticles into P84 and P84/SPEEK precursors and observed that the O /N selectivity of the c-CMSM was higher than that of the non-functionalized CMSM. Yoda et al (2004) reported a 17-fold enhancement of H /N selectivity of CMSM after adding Pt and Pd to polyimide precursors. Hollow-fiber CMSM derived from sulfonated poly(phenylene oxide) (SPPO) were prepared by Yoshimune et al (2006).…”
Section: Introductionmentioning
confidence: 99%
“…These were used to calculate boiling points of the precursors and could be compared to literature values of melting and decomposition temperatures reported in literature [13,14]. The catalysts produced under an argon atmosphere at 2 bars decompose from the liquid phase whereas catalysts produced under a vacuum atmosphere decompose from the vapour phase.…”
Section: Effect Of Catalyst Preparation Atmospherementioning
confidence: 99%
“…Preparation methods for polymer/metal nanocomposites are divided into five groups: (1) metallic precursor solved in a polymer solution is reduced to metallic nanoparticles by adding reducing agent; (2) metallic precursor solved in a monomer is thermally reduced during the polymerization at high temperature; (3) colloidal metallic nanoparticles are mixed with a polymer solution; (4) impregnated metallic precursor into a polymer matrix in a solvent and then treated by a reducing agent or by thermolysis process; and (5) sublimed metallic precursor molecules penetrate into a polymer matrix and are reduced to self-assembled metallic nanoparticles [4][5][6][7]. The methods (1)-(4) are wet processes, while the last method (5) is a dry process.…”
Section: Introductionmentioning
confidence: 99%